Hubungan Rasio Lingkar Pinggang Panggul dengan Penderita Hipertensi pada Lansia di Wilayah Kerja Puskesmas Wire Kabupaten Tuban - Ida Nur Ariyanti; Lilia Faridatul Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
High blood pressure or hypertension is a public health problem in Indonesia. High blood pressure or hypertension is a condition in which blood pressure in the arteries increases consistently above normal limits. This study aims to analyze the relationship between the waist-hip circumference ratio and the incidence of hypertension in the elderly in the Wire Health Center work area of ​​Tuban Regency.This study uses an observational analytical research design with a "Cross-sectional" data collection method. The sample of this study was 163 people who met the inclusion criteria, namely the elderly aged 60 years and over who were willing to be respondents, determined by the Simple Random Sampling technique. With the independent variable ]waist-hip circumference ratio. The dependent variable is hypertension. The analysis of this study used the Spearman Rank correlation statistical test. The results of the study, most of the waist-hip circumference ratios were classified as at risk. The results of the analysis between ]waist-hip circumference ratio and the incidence of hypertension showed a p value of 0.001, there was a significant relationship. From the description above, it can be concluded that the greater the waist-hip circumference ratio, the higher the risk of hypertension in the elderly in the Wire Health Center work area of ​​Tuban Regency.